Experimental Studies on Vegetating Potential on Bare Ground in Antarctica - AYUKAWA , Eri; 5409; 鮎川, 恵理; eriayukawa; アユカワ, エリ; IMURA, Satoshi; 8445; KANDA, Hiroshi; 8817; 神田, 啓史; カンダ, ヒロシ (八戸工業大学, 2005)
110003483488 departmental bulletin paper